Trypanotolerant cattle and livestock development in West and Central Africa. Vol. II. Trypanotolerant cattle in the national economies - Demissie, T.; Kassahun, A.; Yohannes, G. (Institute of Agricultural Research, 1988)
Effects of castration on growth and carcass characteristics were investigated in 54 male Horro lambs grazed on pasture, with two levels of supplementary concentrate fed over a period of 120 days. At the higher level of supplementary feeding, entire lambs showed significantly higher growth rates (144 varsus 75 g/day) and carcass weights (16.9 and 12.3 kg), and significantly less fat thickness over the eye muscle (3.6 versus 6.0 mm) and internal, omental + Kidney, fat (50 versus 99 g) than castrated lambs. All of these measurements were significantly lower but did not differ significantly between entire and castrated lambs at the lower level of supplementary feeding.